Perpetual perishing, perpetual renewal - Rolston, Holmes, 1932-2025, author; Yukon College, publisher (Colorado State University. Libraries, 2008)
Darwinian nature is in dialectic: conflict and resolution. Human life evolved out of such dialectical nature. If that began in Africa, it continues when humans migrate far North. Religious encounters with such nature, whatever their differences with Darwinism, also find that life is perpetually renewed in the midst of its perpetual perishing. Life is ever "conserved," as biologists might say; life is ever "redeemed," as theologians might say. In this generating of new life, nature is cruciform, beyond the dialectical. Such processes, set in their ecological settings, perennially transform disvalues in nature into prolific values, generating the global richness of evolutionary natural history and its exuberance of life. Such sombre beauty in life is nowhere better exemplified than in boreal and Arctic nature.
Keywords: creative nature; cruciform nature; ambivalence; dialectical nature; Arctic/Boreal nature; survival